Plan de negocios para la comercialización y exportación de joyas a base de materiales naturales exóticos hechos a mano - Cantos Quiróz, Rocke Joshua (2015)
Ecuador is a multiethnic and multicultural country with diverse regions that produce various handicrafts that reflect their own culture. CantosandLeiva Corp prepared a business plan to export and commercialize in the international jewelry market at the forefront of fashion, made with representative materials of the Amazon region of Ecuador, such as seeds, fibers, fruit peel with resemblance to wood such as mate, among other natural materials that do not have an impact on the environment. The jewelry is hand made by the inhabitants of the Amazonian sector. These products are perfect for people who care about preserving the environment, they have a low environmental mark, with exclusive and trendy designs. CantosandLeiva Corp products are made with strict social responsibility related and fair trade policies that focus on helping communities that perform these jewelry by hand; especially paying them a fair price for their products...